2003
DOI: 10.1021/jm034173l
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of a Potent and Selective Triazolone-Based Peroxisome Proliferator-Activated Receptor α Agonist

Abstract: A new series of hPPARalpha agonists containing a 2,4-dihydro-3H-1,2,4-triazol-3-one (triazolone) core is described leading to the discovery of 5 (LY518674), a highly potent and selective PPARalpha agonist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
52
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 23 publications
1
52
0
2
Order By: Relevance
“…Although fenobric acid (Willson et al, 2000) does not demonstrate analgesic efficacy after acute administration (Table 1), other fibrates as well as new classes of high-affinity PPAR-␣ ligands have become available (Xu et al, 2003;Singh et al, 2005). These include dual PPAR-␣/PPAR-␥ modulators (Fagerberg et al, 2005) that, by combining the analgesic and antiinflammatory activity of PPAR-␣ with the glucose-lowering properties of PPAR-␥, might offer an innovative therapeutic approach to painful diabetic neuropathies, a condition that afflicts more than 30 million people worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Although fenobric acid (Willson et al, 2000) does not demonstrate analgesic efficacy after acute administration (Table 1), other fibrates as well as new classes of high-affinity PPAR-␣ ligands have become available (Xu et al, 2003;Singh et al, 2005). These include dual PPAR-␣/PPAR-␥ modulators (Fagerberg et al, 2005) that, by combining the analgesic and antiinflammatory activity of PPAR-␣ with the glucose-lowering properties of PPAR-␥, might offer an innovative therapeutic approach to painful diabetic neuropathies, a condition that afflicts more than 30 million people worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a recent publication showed that a potent and selective PPAR␣ agonist, LY-518674 (Xu et al, 2003), in patients with low HDLc and high triglycerides or high LDLc had essentially the same effect as fenofibrate in modulating lipid levels, with a similar level of safety concerns (Nissen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…1,2,4-Триазол-3-оны представляют интерес, главным образом, как фармакологически значи-мые соединения, активность которых зависит от характера заместителей у атомов N-2, N-4 и C-5 [1][2][3][4]. Среди них обнаружены вещества с противоопухолевыми свойствами [1], агонисты PPAR рецепторов [2] и антагонисты нейрокинина 1 (NK 1 ) [3].…”
Section: Introductionunclassified
“…Среди них обнаружены вещества с противоопухолевыми свойствами [1], агонисты PPAR рецепторов [2] и антагонисты нейрокинина 1 (NK 1 ) [3]. 2,5-Биарил-1,2,4-триазол-3-оны и 4,5-биарил-1,2,4-триазол-3-оны известны как активаторы калиевых (Maxi-K2) каналов [4].…”
Section: Introductionunclassified